Die verband tussen skeppingsordinansies en kulturele vormgewing by A. Kuyper - Walt, M. F. van der (Koers, 1995)
The relationship between creational ordinances and cultural formations (as seen by A. Kuyper). The central statement of this article is that Abraham Kuyper does not make a clear enough distinction between divine normative creational ordinances on the one side, and human cultural structures on the other. Kuyper defines this relationship in a semi-deterministic (organistic) way. The reason for this semi-deterministic approach can be found in Kuyper’s neo-Platonic logos-speculation and his Romantic-Idealistic use of the organism metaphor. Such a semi-deterministic approach can easily lead to cultural conservatism (for example political conservatism). The proposed answer to Kuyper’s problematic approach implies the following:• Cultural activities should always be seen as free formative action and should not be regarded in a semi-deterministic way.• Cultural activities should always be seen as being partially the result o f the brokenness o f man. Consequently, our knowledge o f divine ordinances as reflected in these activities will always be provisional.• Cultural activities should always be seen against the background of the divine facilitating structure o f the creational ordinances.